A educação segundo o olhar da Veja: uma análise linguístico discursiva da representação dos atores sociais da educação - Chagas, Rita Maria Fonseca Matos (2010)
The aim of the present study is to investigate the ways in which social actors in Education (teachers, students and school) are represented in the reportages of the magazine Veja, year 2007, Education Sector. At first, the objective is to analyze the linguistic and ideological strategies mobilized by enunciators to represent social actors in building its image to the reading public. Secondly, it is our intention to present, through the analyses of these representations, the ethical and political developments arising out of these representations. To guide the research it is risen the possibility that Veja, grounding on neoliberalist philosophical assumptions and technicist pedagogy, builds for the reading public an ideal image of education, incorporating the educational system, teachers and students in pre-established models as the only means for solving problems in teaching and learning and, with that doing, naturalize hegemonic practices and stresses the ethical issue of social exclusion. Due to the interdisciplinary and interventionist nature of research, is chosen as the theoreticalmethodological apparatus, the qualitative interpretative paradigm, as discussed by Moita Lopes (1994), Signorini (1998), Cavalcanti (1996), Gialdino (1993), among others. It is used as theoretical foundation for the analyses, the assumptions of Critical Discourse Analysis, as discussed by Fairclough, (2001a, 2001b), Pedro (1997), Resende and Ramalho (2006), among others. The notions of ideology are presented as per contributions by Thompson (1995), Van Leeuwen (1997) and the notions of power are presented in accordance with the studies by Foucault (2000). A Critical Discourse Analysis considers some fundamentals of Functionalist Linguistics and accordingly, we use the contributions by Halliday (1994), Eggins (1994), Neves (2006), among others. We present some ideas about intertextuality, focusing on the heterogeneity of the texts and the discursive formations, as contributions by Bakthin (2003), among others. We study the ethos (AMOSSY, 2008), gender (MEURER; BONINI, Motta ROTH, 2005) and the assumptions of neo-liberal philosophy and technicist pedagogy. In addition to the hypothesis proved through the analyses, it was found that the reportages were characterized as article and, therefore, it is asserted that Veja reportages presented an opinionated angle masquerading as information. It was concluded also, through analyses, that the social actors of education were represented as objects and as ends in themselves to serve a larger project: to supply the market.